(untitled) (Terr@ Plural, 2019)
This work is based on a bibliometric review aiming to provide an overview of the use of geotechnology applied to plan and management in medium-sized cities, as outlining the main trends and gaps, Scopus was selected as the key database for this study, considering its global use in the academic setting. The researched key terms appear only in 2007, evidencing the lack of papers about medium cities in high-performance journals. It was highlighted predictive models of urban sprawl and assessment of the ecological safety level of cities. Major innovations have adopted multiple satellite data sources, programming validation and optimization routines of image classifying algorithms, as well as the increment of semi-automated open and open-source processing chains. Given the various applications derived from geotechnologies, the adoption of these tools by municipal secretariats is essential to replace the archaic or inefficient territorial planning and management.